Badanie zróżnicowania województw Polski pod względem innowacyjności za pomocą wybranych metod taksonomicznych - Surówka, Agata (The research of the voivodships diversity in Poland in terms of innovativeness with application of the selected taxonomic methods, 2008)
Innovativeness is a concept of a complex character that is why it is defined differently in various literature. In the conducted empirical research it was regarded as a multidimesional variable. In order to illustrate the differentiation of the voivodships in Poland in the respect of innovativeness the methods of linear order and the method of Ward classification were applied. The results allowed to show the differentiation of voivoships taking into account variables which define innovativeness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 150-161